Sub-pixel multi-scale fusion network for medical image segmentation - Li, Jing; Chen, Qiaohong; Fang, Xian (Multimedia tools and applications, 2024)
CNNs and Transformers have significantly advanced the domain of medical image segmentation. The integration of their strengths facilitates rich feature extraction but also introduces the challenge of mixed multi-scale feature fusion. To overcome this issue, we propose an innovative deep medical image segmentation framework termed Sub-pixel Multi-scale Fusion Network (SMFNet), which effectively incorporates the sub-pixel multi-scale feature fusion results of CNN and Transformer into the architecture. In particular, our design consists of three effective and practical modules. Primarily, we utilize the Sub-pixel Convolutional Module to synchronize the extracted features at multiple scales to a consistent resolution. In the next place, we develop the Three-level Enhancement Module to learn features from adjacent layers and perform information exchange. Lastly, we leverage the Hierarchical Adaptive Gate to fuse information from other contextual levels through the Sub-pixel Convolutional Module. Extensive experiments on the Synapse, ACDC, and ISIC 2018 datasets demonstrate the effectiveness of the proposed SMFNet, and our method is superior to other competitive CNN-based or Transformer-based segmentation methods.